Many names, many gains? How local diversity in Germany affects innovation - Anna Kremer (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2025)
Meeting others with different backgrounds brings up new ideas. This paper shows that this not only matters for a background in heterogeneous industries or nationalities, but that regional differences matter too. Regions within a country vary in their traditions and culture. Cultural homogeneity within regions becomes mixed due to internal migration, which, like international migration, increases the diversity of a place. In a novel approach, I look at diversity in German municipalities, measured by different family names, and investigate its effect on the number of generated patents. I use a unique dataset from a 1996 phonebook and casualty lists from WWI. There is a positive association between innovation and diversity when defined by the share of new names, a deconcentration measure, or a Shannon index. Causality is established by using instrumental variables estimations with historical borders. I show that intra-country diversity affects patenting positively and conclude that regional differences matter for economic outcomes.
urn:nbn:de:bsz:14-qucosa2-1004928
Keywords: R11; O30; Z13; 330; cultural diversity; innovation; family names; patents; local level; Germany